Energy Efficient Load Balancing Technique for Distributed Data Transmission Using Edge Computing - Karthikeyan, K; Madhavan, P (Role of Edge Analytics in Sustainable Smart City Development, 2020)
Nowadays, various IoT devices are connected through the internet to the cloud. With that there is huge amount of data to be transmitted through cloud. Cloud is purely supportable for centralized data processing. In a centralized processing system, handling large amount of data leads to higher latency thereby reducing the efficiency. Load balancing also playing a vital role in the centralized processing. To toggle this problem, edge computing platforms has to be implemented. These kinds of edge computing platforms allow some application to be performed by small edge server positioned between cloud and the user. The edge computing is a convergence of IT and telecom networking. It is a distributed cloud computing environment which supports offloading of data transmission. The edge computing is not a new concept which is expanded versions of cloud computing, with that all computations are done at the edge of the network. In this, data does not need to be sent to remote cloud or other centralized systems for processing. It removes processing latency as the data need not be sent from the edge of the network to a central processing system. Edge computing is essentially cloud principles applied at network edge close to the user. The usage of distributed algorithm in edge computing platform leverages latency and balances the work load of the request and response.